Purification and Characterization of O-Methyltransferase I Involved in Conversion of Demethylsterigmatocystin to Sterigmatocystin and of Dihydrodemethylsterigmatocystin to Dihydrosterigmatocystin during Aflatoxin Biosynthesis - Yabe, Kimiko (American Society for Microbiology, 1998)
O-Methyltransferase I, which catalyzes conversions both of demethylsterigmatocystin (DMST) to sterigmatocystin (ST) and of dihydrodemethylsterigmatocystin (DHDMST) to dihydrosterigmatocystin (DHST) during aflatoxin biosynthesis, was purified to apparent homogeneity from the cytosol fraction of the mycelia of Aspergillus parasiticus NIAH-26 through the following chromatography series: phenyl-Sepharose, DEAE-Sepharose, phenyl-Sepharose, Sephacryl S-300, and Matrex gel Green A. The apparent molecular mass was estimated at 150 kDa based on Sephacryl S-300 gel filtration chromatography, and the denaturing molecular mass was 43 kDa based on sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The pI of the enzyme was 4.4, and the optimal pH for activity was broad, from 6.5 to 9.0. In competition experiments using the purified enzyme, the formation of ST from DMST was suppressed when DHDMST was added to the reaction mixture and DHST was newly formed. These results indicate that DMST and DHDMST commonly serve as substrates for the enzyme. The K(m) of the enzyme for DMST was 0.94 μM, and that for DHDMST was 2.5 μM. Interestingly, MT-I kinetics deviated substantially from standard Michaelis-Menten kinetics, demonstrating substrate inhibition at a higher substrate concentration.